Self-Actualization as an Embodiment of the Evaluative Potential of the concept WORK - Blagodarna, O.M. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
This article examines the correlation between the main theses of A. Maslow self-actualizing theory and the evaluative component of the concept WORK. The latter is objectivized by its name, the lexeme work, its synonyms, derivatives that belong to different parts of speech, free and phraseological phrases. Cognitive interpretation of the meanings of the concept WORK verbalizations has demonstrated that its notional- and image-evaluative content reflects the major stages of selfactualization, while the concept itself gains additional evaluative overtones.
Keywords: concept; notional- and image-evaluative content; self-actualizing theory